+0  
 
0
61
1
avatar

If \(\omega^3 = 1\) and \(\omega \neq 1\), then compute \((1 - \omega + \omega^2)(1 + \omega - \omega^2)\).

 Jan 13, 2020
 #1
avatar+107405 
+1

Note that 

w^3  = 1

w^3 - 1    = 0

(w - 1) (w^2 + w + 1)    = 0

 

So either   

w - 1  =  0      reject  because  w  cannot = 1       or

w^2 + w + 1  = 0

 

So.....

 

( 1 - w + w^2)  ( 1 + w - w^2)  =

 

[ ( 1 + w + w^2) - 2w ]  [ (1 + w  + w^2) - 2w^2 ]  =

 

[    ( 0)  - 2w ]  [ (0) - 2w^2 ]  =

 

[ -2w ] [ -2w^2 ]  =

 

4w^3  = 

 

4(1)   = 

 

 

 

cool cool cool

 Jan 13, 2020

14 Online Users

avatar